DINAMIKA HUBUNGAN ANTAR ETNIS DAN INTEGRASI IMIGRAN DI INGGRIS - Pundan Rama; Tri Cahyo Utomo; Reni Windiani (Journal of Politic and Government Studies, 2013)
AbstractThis paper attempts to describe the dynamics of inter-ethnic relationships, theintegration of ethnic groups in Britain, and how the UK government react to it. Researchdesign that used in this paper is qualitative with descriptive method. The data used in thispaper in the form of secondary data obtained from various sources.Britain as a multicultural country is faced with the challenge of managing inter-ethnicrelations in order to maintain peaceful society. Inter-ethnic relations in the UK experiencingtension until now, mainly due to four things the racial riots, incidents involving the killing ofa particular ethnic, racial sentiments, and racism. Race riots broke out in the Britain a fewtimes which resulted in heated inter-ethnic relations. In addition, the murder incidentsinvolving a particular ethnic group often creates a bad atmosphere of inter-ethnic relationsin Britain. Racial sentiment and institutional racism that still exist in some institutions inBritain, helped trigger frictions between ethnic groups as well. In this case, the mass mediaalso plays a major role in triggering inter-ethnic friction that occurs. However, inter-ethnicrelations in the UK also has moments of harmony, especially when the Race Relations Act of1976 was passed and the anti-racism organization was formed.The dynamics of inter-ethnic relationships in Britain are caharacterized by a numberof incidents so that led to debate about the integration of immigrants and minority ethnicgroups with the British society. The integration can be viewed through four dimensions: thedimension of cultural, social, economic, and political. Research by public institutions andofficial statistics owned by UK government show that ethnic minorities in Britain have notbeen fully integrated with British society. This was demonstrated by the fact that someminority ethnic groups in Britain have little opportunity to access resources to meet theirneeds. The causes are varied, ranging from individual factors to environmental factors. Inresponse, the British government has issued a policy that aims to increase opportunities forthe integration of ethnic minorities. Nevertheless, it needs to be supported by efforts to createa broader public space so that each ethnic group get to know one another.Key words: the dynamics of relationships, ethnic group, UK, integration